Together Is Better: The Rumen Microbial Community as Biological Toolbox for Degradation of Synthetic Polyesters - Quartinello, Felice; Kremser, Klemens; Schoen, Herta; Tesei, Donatella; Ploszczanski, Leon; Nagler, Magdalena; Podmirseg, Sabine M.; Insam, Heribert; Piñar, Guadalupe; Sterflingler, Katja; Ribitsch, Doris; Guebitz, Georg M. (Frontiers in Bioengineering and Biotechnology, 2021)
Microorganisms, like bacteria and fungi, are becoming an emerging resource for the development of eco sustainable plastic degradation and recycling processes. In this study, the rumen content from cattle (Bos taurus) was investigated regarding synthetic polyester hydrolyzing enzymes based on the fact that the diet of ruminants may contain natural plant polyesters. A screening with model substrates demonstrated hydrolytic activities of rumen fluid on p-NP-esters with 4 to 8 carbon atoms. Rumen fluid hydrolyzed synthetic aromatic polyesters with higher amounts of terephthalic acid released from poly(butylene adipate-co-terephthalate (PBAT) (0.75 and 0.5 mM for polymer powder and film, respectively) and thus exceeded when compared to the hydrolysis of the second terephthalic acid-based polymer- poly(ethylene terephthalate) (PET) (0.6 and 0.15 mM, for powder and film, reciprocally). Additionally, rumen fluid hydrolyzed the bio-based polyester poly(ethylene furanoate) (PEF) according to HPLC and SEM analysis. Environmental metagenomic analysis of the rumen microbial community revealed a composition of bacteria (98%), followed by Eukaryota (1%) and finally Archaea. Among the most abundant genera encountered in this study, polyester hydrolysis activity has already been proved (e.g. Pseudomonas).